Acute liver failure due to white phosphorus ingestion (2009)
ABSTRACT: Background: White phosphorus is chemical compoundavailable in military ammunition as well as in explo-sive powder of recreational use. This latter form iscommonly found in Latin America and Asia as a mainingredient of gunpowder used to make street firecrack-ers. Small firecrackers may be ingested accidentally orused as a toxic agent in suicidal attempts which maycause of acute liver failure and death; however the clin-ical features, incidence and outcome are poorly de-scribed in the literature. Methods: We describe threecases of white phosphorus intoxication with acute liverfailure secondary to the consumption of firecrackers.In two cases, ingestion occurred secondary to suicidalattempts and in one, ingestion occurred by accident. Inone case, liver injury improved with supportive care,in the other, the patient required liver transplantationand the third case had a fatal outcome. Conclusions:Clinicians providing care of patients with acute hepati-tis of unclear etiology should be aware that the inges-tion of firecrackers containing white phosphorus might cause acute liver failure that may require liver trans-plantation.